Pengaruh Tinggi Unggun Karbon Aktif Dan Pasir Kuarsa Pada Saringan Pasir Lambat Untuk Penyisihan Logam Fe Pada Air Sungai Siak - Putriani Putriani; Shinta Elystia; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Siak river water into the many natural resources provide benefits for the inhabitants of nearby, but the condition of the river siak currently included in the critical category. One of the treatments to reduce levels of pollutants in river water is by using a slow sand filter using quartz sand and activated carbon. This research aims to determined the effect of high activated carbon and quartz sand as well as the best sampling time with the efficiency of removal of Fe parameters in slow sand filters, and compared the quality standards of PP No. 82 of 2001. The fixed variable uses in this research is the velocity of water flow on the sand filter is slow 0.3 m / hour and the sampling time is 0, 15, 30, 45, 60. The changeable variable uses consists of variations in bed height in the reactor namely : 10 cm gravel, 50 cm quartz sand, and 20 cm activated carbon; 10 cm gravel, 60 cm quartz sand, and 10 cm activated carbon; and 10 cm gravel, 70 cm quartz sand, and no activated carbon. Based on the results of the research after the slow sand filtering process obtained the best removal efficiency in reactor 1 for 60 minutes, the efficiency of removal of Fe metal by 97.52%.Keywords: Siak River, Slow Sand Filter, activated carbon, quartz sand, Fe metal removal.